RETRACTED: Heart transplant in a patient with persistent left superior vena cava - G. V. Aniskevich; G. A. Sadrieva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
RETRACTEDTA clinical case of successful orthotopic heart transplantation using the biatrial technique with the displacement of the persistent left superior vena cava into the right atrium. The achieved clinical effect as a result of the treatment fully justifies the chosen surgical tactics and allows us to recommend the proposed tactics for the treatment of such a rare pathology.